Pengaruh Audit Committee, Audit Quality, Financial Stability dan Financial Target Terhadap Financial Statement Fraud pada Perusahaan Transportasi yang Terdaftar pada BEI Tahun 2021-2022 - Dinillah, Syifa; Djamil, Nasrullah (MUI Kota Pekanbaru, 2024)
This study investigates the impact of four independent variables, namely Audit Committee, Audit Quality, Financial Stability, and Financial Target, on the dependent variable Financial Statement Fraud. The sample was selected from the population of transportation companies listed on the Indonesia Stock Exchange (IDX) during the period 2021-2022 using purposive sampling method. Through the application of panel data regression analysis, this study has determined that the Audit Committee, Audit Quality, and Financial Stability significantly influence the prevention of Financial Statement Fraud in transportation companies listed on the IDX during the studied period. The findings indicate that an effective Audit Committee and high Audit Quality are crucial in reducing the risk of financial statement fraud by maintaining the integrity and reliability of financial statements. Additionally, Financial Stability contributes to agency dynamics that discourage financial statement fraud. Meanwhile, the variable Financial Target did not have a significant effect on Financial Statement Fraud, indicating that the targets set by the company do not directly contribute to the occurrence of financial statement fraud. These results suggest the importance of the role of internal and external audits in overseeing the integrity of financial statements and emphasize the need for financial stability to reduce the risk of financial statement fraud in the transportation sector.